Genetic diversity of the pampas deer (Ozotoceros bezoarticus) population in the Brazilian pantanal assessed by combining fresh fecal DNA analysis and a set of heterologous microsatellite loci - Mantellatto, Aline Meira Bonfim [UNESP]; Caparroz, Renato; Christofoletti, Maurício Durante [UNESP]; Piovezan, Ubiratan; Duarte, José Maurício Barbanti [UNESP] (FapUNIFESP (SciELO), 2017)
The pampas deer (Ozotoceros bezoarticus) is close to being classified as globally threatened’, with the largest population occurring in the Brazilian Pantanal. Since capture is stressful to these animals, non-invasive sampling methods such as the use of feces can provide reliable sources of DNA. The aim of this study was to use fecal samples to evaluate the genetic variability of the Brazilian Pantanal population of pampas deer. Six heterologous microsatellite markers were used to screen 142 stool specimens. Seventy-four deer were identified, of which 50 adults were used to determine the genetic characteristics of the population. The Pantanal population showed high genetic diversity (mean number of alleles per locus = 11.5, expected heterozygosity = 0.75). This is the first investigation to characterize a South American deer species using fecal DNA and demonstrates the usefulness and efficiency of this approach, as well as the feasibility of obtaining information that could not have been easily obtained by traditional DNA sampling. Our findings suggest that management strategies for this species may be much more effective if applied now when the population still shows high genetic variability.
Keywords: Conservation; Fecal DNA; Microsatellites; Non-invasive methods; Pampas deer